PREVALENCE, RISK FACTOR, MANAGEMENT AND OUTCOME OF RESISTANT HYPERTENSION: SYSTEMATIC REVIEW - Azwar Aziz, Mohamad; Intan Kania, Yulia; Aziz, Ilham; Sibli, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Resistant hypertension (RH) increases the morbidity and mortality from stroke and cardiovascular disease in comparison to hypertension without treatment resistance.Aims : This systematic review is to review the prevalence, risk factor and management of resistant hypertension.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 1032 articles, whereas the results of our search on SAGEPUB brought up 29093 articles, our search on SCIENCE DIRECT brought up 96059 articles. The results of the search conducted for the last year of 2014 yielded a total 556 articles for PubMed, 12517 articles for SAGEPUB and 43884 articles for SCIENCE DIRECT. In the end, we compiled a total of  9 papers, 4 of which came from PubMed, 1 of which came from SAGEPUB and 4 of which came from SCIENCE DIRECT. We included nine research that met the criteria.Conclusion: In summary, the therapy of lowered heart rate includes improving lifestyle modifications, utilizing long-acting thiazide-like diuretics, adding a mineralocorticoid receptor antagonist, and gradually adding antihypertensive drugs with complementary modes of action if blood pressure does not decline.